2015
DOI: 10.1007/s00228-015-1825-z
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the use of potentially inappropriate drugs among old people living in geriatric care units between 2007 and 2013

Abstract: The extent of potentially inappropriate drug use declined between 2007 and 2013 according to the quality indicators used. Medication reviews involving clinical pharmacists might be an important factor in reducing potentially inappropriate drug use and improving drug treatment among old people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
31
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 43 publications
10
31
0
Order By: Relevance
“…A longitudinal follow-up is planned for 2018 and other future national and international studies can compare those results with the results from this study. The results show a cognitive impairment prevalence rate of 67 %, which is in line with earlier studies in similar contexts which indicate prevalence rates of 71–73 % [6, 7]. This finding is also in line with a European study including 4156 residents in eight countries (the Czech Republic, England, Finland, France, Germany, Italy, The Netherlands and Israel) which shows an overall prevalence of cognitive impairment of 68 % [3].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A longitudinal follow-up is planned for 2018 and other future national and international studies can compare those results with the results from this study. The results show a cognitive impairment prevalence rate of 67 %, which is in line with earlier studies in similar contexts which indicate prevalence rates of 71–73 % [6, 7]. This finding is also in line with a European study including 4156 residents in eight countries (the Czech Republic, England, Finland, France, Germany, Italy, The Netherlands and Israel) which shows an overall prevalence of cognitive impairment of 68 % [3].…”
Section: Discussionsupporting
confidence: 92%
“…Cognitive and physical impairments are two of the factors most associated with nursing-home admission [1] and both cognitive and ADL impairments have been shown to be common in nursing homes internationally [2–5]. Two previous studies in Sweden show that cognitive impairment among nursing-home residents was prevalent in 71 % (2008) [6] and 73 % (2013) [7] respectively of all cases. However, these studies were limited because of their regional context and, in the case of the first one, also regarding their sample size ( n  = 315).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cooperation between workers may have contributed to valuable exchanges of views and knowledge. There is evidence that medication reviews based on medication lists and PHASE-20 can reduce the number of inappropriate medications (Milos et al, 2013;Gustafsson et al, 2015). The rapid spread and extensive use of PHASE-20 in Sweden also indicate that clinicians find it a useful and worthwhile tool.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, it has been shown that pharmacist-led medication reviews based on medication lists and PHASE-20 reduce potentially inappropriate medications in people aged 75 years or older in primary health care (Milos et al, 2013) and among residents in nursing homes (Gustafsson et al, 2015). PHASE-20 is recommended in the Quality indicators for good drug therapy in the elderly, which was developed by the Swedish National Board of Health and Welfare (2010), and is currently used in all counties in Sweden.…”
Section: Introductionmentioning
confidence: 99%